C-modified stacking-fault networks inducing the excellent strength- plasticity combinations of medium manganese steel by simple two-stage warm rolling without annealing. (May 2023) - Zhang, Yingchao; Song, Renbo; Wang, Yongjin; Cai, Changhong; Wang, Haibo; Wang, Kaikun
Abstract: The medium manganese steel with ultrahigh yield strength of 1421 MPa, a tensile strength of 1575 MPa, and an excellent total elongation of 28.4% was designed by simple two-stage warm rolling without annealing. The improvement of yield strength is mainly attributed to the extensive strengthening defects in the lamellar dual-phase microstructures, which including the high-density dislocations in ferrites and high-density dislocations, nanoscale VC precipitates, stacking faults and Lomer-Cottrell (L-C) locks in austenite (22 Vol.%). In addition, the abnormally enhanced strain-hardening ability benefits from the C-modified stacking-fault networks, whose stability and C-segregated characteristics are precisely clarified by the advanced in-situ heating HRTEM and APT analysis. This special strengthening and plasticizing effects of stacking faults induced by simple two-stage warm rolling can effectively break through the trade-off between strength and plasticity of ultra-strong medium manganese steel. Graphical abstract: Image, graphical abstract